(untitled) (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2024)
Enterprise Identity and Access Governance (IAG) is undergoing a fundamental transformation driven by cloud adoption, hybrid workforce dynamics, regulatory intensification, and the proven inadequacy of periodic, manual access certification in managing the risk of excessive entitlements. This paper presents the Adaptive Identity and Access Governance Framework (AIAGF), a production validated intelligent IAG platform that integrates Graph Neural Network (GNN)based identity risk scoring, AI assisted access certification, MLdriven role mining, and continuous privilege lifecycle governance across heterogeneous enterprise identity ecosystems. AIAGF introduces two novel algorithms: Algorithm 1 (AIAGF) constructs a dynamic identity entitlement knowledge graph, applies Louvain community detection for peer group formation, and computes a five factor composite risk score per identity using weighted ensemble of GNN node embeddings, Bilt behavioral analysis, SoD conflict scoring, peer deviation metrics, and historical pattern analysis. Algorithm 2 (IARS: Identity and Access Risk Scoring Engine) formalizes the multidimensional risk computation with Platt scaled probability calibration and Shape based explainability. The framework’s access certification module achieves 64.3% AI precertification rate, reducing mean campaign duration from 97 days to 10.7 days while maintaining 98.4% certification accuracy. Driven role mining reduces role explosion from 8,241 to 1,134 business roles (86% reduction) achieving silhouette coefficient 0.71, with SoD conflicts reduced 94%. Experimental evaluations across 28 enterprise organizations (247,000 identities, 18month longitudinal study) demonstrates: 98.4% identity risk classification accuracy (AUC 0.981), 74% reduction in access violations, 89% certification cycle time reduction, and average 3.4M annual cost avoidance per organization. Comparative analysis against SailPoint Identity Now, Saviynt Enterprise, IBM Security Verify, One Identity Manager, and rule based baselines confirms AIAGF superiority across all metrics (McNemar’s test, p < 0.001).